Practical WebAssembly: Explore the fundamentals of WebAssembly programming using Rust - Nellaiyapen, Sendil Kumar (Packt Publishing, 2022)
Understand the basic building blocks of WebAssembly and learn, install, and use various tools from the Rust and WebAssembly ecosystem Key Features Understand the Rust programming language and WebAssembly concepts for web developmentBuild web, mobile, and embedded apps using WebAssemblyEnhance the scalability and resilience of your web apps Book Description Rust is an open source language tuned toward safety, concurrency, and performance. WebAssembly brings all the capabilities of the native world into the JavaScript world. Together, Rust and WebAssembly provide a way to create robust and performant web applications. They help make your web applications blazingly fast and have small binaries. Developers working with JavaScript will be able to put their knowledge to work with this practical guide to developing faster and maintainable code. Complete with step-by-step explanations of essential concepts, examples, and self-assessment questions, you’ll begin by exploring WebAssembly, using the various tools provided by the ecosystem, and understanding how to use WebAssembly and JavaScript together to build a high-performing application. You’ll then learn binary code to work with a variety of tools that help you to convert native code into WebAssembly. The book will introduce you to the world of Rust and the ecosystem that makes it easy to build/ship WebAssembly-based applications. By the end of this WebAssembly Rust book, you’ll be able to create and ship your own WebAssembly applications using Rust and JavaScript, understand how to debug, and use the right tools to optimize and deliver high-performing applications. What you will learn Explore WebAssembly and the different tools available in the WebAssembly ecosystemUnderstand the raw WebAssembly binary and the WebAssembly text formatUse the Web and JavaScript API with wasm-bindgenOptimize Rust and WebAssembly for high performanceRun and debug WebAssembly and Rust codeExplore various tools available in the RustWASM ecosystem Who this book is for This book is for JavaScript developers who want to deliver better performance and ship type-safe code. Rust developers or backend engineers looking to build full-stack applications without worrying too much about JavaScript programming will also find the book useful.